2014
DOI: 10.1111/oik.01359
|View full text |Cite
|
Sign up to set email alerts
|

Climate warming delays and decreases seedling emergence in a Mediterranean ecosystem

Abstract: Temperature and moisture impact strongly on the early stages of a plant ' s life cycle. Global climate change is altering the environmental cues that seeds receive resulting in compromised seedling emergence and changes to seedling performance. Here, we investigate how temperature and moisture aff ect these early stages of plant development in four Banksia species collected from a longitudinal climate gradient in South West Western Australia. A common garden was used to examine the between-species and among-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 58 publications
(70 reference statements)
3
46
0
Order By: Relevance
“…Banksia coccinea had a greater number of small leaves with higher specific leaf area, but accumulated less overall biomass compared to B. baxteri when grown under favourable conditions. These differences in leaf size and specific leaf area are also supported by previous investigations on adult plants (Cochrane et al 2014a) and seedlings of these same species (Cochrane et al 2014b). Theory suggests that the greater the difference in functional traits between species pairs, the more likely there will be strong differences in response to limiting factors (Adler et al 2013).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Banksia coccinea had a greater number of small leaves with higher specific leaf area, but accumulated less overall biomass compared to B. baxteri when grown under favourable conditions. These differences in leaf size and specific leaf area are also supported by previous investigations on adult plants (Cochrane et al 2014a) and seedlings of these same species (Cochrane et al 2014b). Theory suggests that the greater the difference in functional traits between species pairs, the more likely there will be strong differences in response to limiting factors (Adler et al 2013).…”
Section: Discussionsupporting
confidence: 55%
“…Seedlings recruit in the autumn-winter wet season, generally post-fire, with the dry summer conditions a main impediment to seedling survival. Previous research has revealed some basic differences between the species: seed mass, adult leaf nitrogen per unit area and above-ground seedling biomass are significantly higher in B. baxteri but adult and seedling specific leaf area (SLA), seedling leaf production rate and time to emergence are significantly lower in comparison to B. coccinea (Cochrane 2014;Cochrane et al 2014a). Furthermore, B. baxteri has higher germination under conditions of moisture stress and higher than optimum temperatures for germination (Cochrane et al 2014b).…”
Section: Introductionmentioning
confidence: 98%
“…2); results that are in agreement with some previous studies (De Frenne et al, 2012;Richter et al, 2012). However, in the southwest of Western Australia, Cochrane et al (2015) found that emergence of seedlings was delayed with warmer conditions, compared to control. It has been previously suggested that early emergence is a strong determinant of seedling vigour and can significantly increase plant biomass (Verdú and Traveset, 2005).…”
Section: Factorsupporting
confidence: 83%
“…To improve our capacity to reinstate biodiverse, viable plant communities, there is a strong need to advance our understanding of how these systems function and the effects that environmental and edaphic factors have on processes such as seedling emergence and plant growth and survival (Perring et al, 2015). For example, changes in soil water availability as a consequence of reduced rainfall and evaporation, or increases in temperature due to global warming, may affect restoration outcomes through influencing seedling recruitment (Cochrane et al, 2015;Lloret et al, 2004) or the composition and distribution of plant species (Lai et al, 2015). But the impact of environmental factors on restoration can be also compounded by unfavourable edaphic conditions (Audet et al, 2013;Thomas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Contrasted with seed release at maturity, canopy seed storage (i.e., serotiny) is reviewed in [153] and we do not extensively discuss canopy-stored seed banks in this chapter. Global warming is expected to reduce seedling emergence for some species [154,155]. Moreover, the evolution of seed dormancy is favored by high seed persistence in the soil seed bank to alleviate the cost of delayed germination [156].…”
Section: Introductionmentioning
confidence: 99%